-7(2x-8)+2x=6(x+8)

Simple and best practice solution for -7(2x-8)+2x=6(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(2x-8)+2x=6(x+8) equation:


Simplifying
-7(2x + -8) + 2x = 6(x + 8)

Reorder the terms:
-7(-8 + 2x) + 2x = 6(x + 8)
(-8 * -7 + 2x * -7) + 2x = 6(x + 8)
(56 + -14x) + 2x = 6(x + 8)

Combine like terms: -14x + 2x = -12x
56 + -12x = 6(x + 8)

Reorder the terms:
56 + -12x = 6(8 + x)
56 + -12x = (8 * 6 + x * 6)
56 + -12x = (48 + 6x)

Solving
56 + -12x = 48 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
56 + -12x + -6x = 48 + 6x + -6x

Combine like terms: -12x + -6x = -18x
56 + -18x = 48 + 6x + -6x

Combine like terms: 6x + -6x = 0
56 + -18x = 48 + 0
56 + -18x = 48

Add '-56' to each side of the equation.
56 + -56 + -18x = 48 + -56

Combine like terms: 56 + -56 = 0
0 + -18x = 48 + -56
-18x = 48 + -56

Combine like terms: 48 + -56 = -8
-18x = -8

Divide each side by '-18'.
x = 0.4444444444

Simplifying
x = 0.4444444444

See similar equations:

| 4x+50=2x+90 | | 2x+17=89-6x | | 4(w-1)=6w+1-2(-6w-1) | | 8x+8=x+1 | | 2x(x-5)-(x-3)(x+2)=28-3(3x-1)(3x+2) | | t/27=-4 | | 2.5/y=5/12 | | 0.557=1-2.557*x | | 7/11=y/99 | | 4/9=24/z | | x^2-11x-51=0 | | x(x+1)=650 | | Y/12=2/3 | | 8y^7-7y^8=0.75 | | Y=8.5x-4 | | 4(3x-2)=2(5x-4) | | Tan^2x-secx=1 | | -3x-4(x+6)=-119 | | (3x-12)/(9-x) | | 16-6(x+12)=-2 | | 16-6(x-12)=-2 | | 8/4-6x3-4 | | 0.50/X=5/161.25 | | (o.50/X)=5/161.25 | | IK=3x+19 | | IK=3x | | HJ=22+2x | | 4(3-x)+x=22+2 | | 4a^2+8a=2 | | 5/18-4x/3=11/6 | | n-40-26=-3 | | -61=61*ln(x/120) |

Equations solver categories